New results with integer formulations for the Capacitated Location-Routing Problem. - Belenguer, José-Manuel; Benavent, Enrique; Prins, Christian; Prodhon, Caroline; Wolfler Calvo, Roberto (HAL CCSD, 2006)
International audience